IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DAN DANA DESA TERHADAP PEMBANGUNAN DI DESA TATELU RONDOR KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Stenly Pangerapan (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2018)
Allocation of Village Funds including Village Funds in its implementation is carried out by several regional government institutions, namely the first local government itself as the regulator or policy maker of use and utilization, secondly the sub-district government and related technical agencies that play a supervisory, mentoring and facilitator role and the third and final is the village government itself as the recipient, user and user of the fund. the implementation of village fund allocation policies in development in the village of Tatelu Rondor, Dimembe Subdistrict, North Minahasa Regency through physical development in the village did not work well, this condition was based on facts namely lack of proper and correct understanding of village government, unavailability of resources adequate in supporting the smooth implementation of village fund allocation policies, lack of communication in supporting implementation activities, lack of support from some village officials and the community, and bureaucratic structures often hampered.